3D‐Printed Pneumatically Controlled Soft Suction Cups for Gripping Fragile, Small, and Rough Objects. (1st July 2021) - Koivikko, Anastasia; Drotlef, Dirk-Michael; Dayan, Cem Balda; Sariola, Veikko; Sitti, Metin
Abstract : A 3D‐printed pneumatically actuated soft suction gripper with an elastomer film is proposed. Suction in such gripper is actively controlled by applying a negative pressure behind the film. The elastomeric gripper body is 3D‐printed, making it easy to customize and integrate into future robotic gripping systems. The gripper can pick a wide variety of objects, such as delicate fruits, small parts, and parts with uneven loads, with high pull‐off forces (over 7.4 N with ∅ 20 mm/55 kPa). The achieved pull‐off forces are significantly higher than the previously reported suction cup grippers with films and more comparable with commercial vacuum grippers. The pull‐off forces show no significant differences with surfaces of varying roughness (up to root‐mean‐square roughness of 5.66 μm) and the gripper is able to pick and release target objects repeatedly. The gripper is also compared with a commercial vacuum gripper with comparable dimensions. It outperforms the commercial gripper in the case of fragile objects, objects smaller than the gripper diameter, and objects with uneven loads. It can apply high pull‐off forces while having controllable release, and is suitable for gripping a wide variety of real‐world objects, including heavy, rough, small, thin, and fragile ones. Abstract : A 3D‐printed soft suction gripper covered with a thin elastomer film is proposed. The gripper can achieve high pull‐off forces (over 7.4 N with ∅ 20 mm/55 kPa) even with rough surfaces and grip a wide variety of real‐world objects, including heavy, rough, small, thin, and fragile ones.